Gambaran Konsep Diri Ibu Menopause di Desa Sumur: Self-Concept Description of Menopausal Mothers in Sumur Village - Eka Martalia; Liyanovitasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
Data from the Central Bureau of Statistics shows that out of 118 million women, 15.2 million experience menopause. Menopause is not only marked by the cessation of menstruation, postmenopausal women also experience many changes, ranging from physical appearance, psychological condition to sexual desire. In addition, menopausal women also can not get pregnant anymore. The changes that occur can have an impact on the self-concept of the mother who experiences it. Self-concept consists of self-image, self-ideal, self-role, self-identity and self-esteem. to know the self-concept description of menopausal women in Sumur Village. This type of quantitative approach with a descriptive design. The study population was 157 menopausal women in Sumur Village with a total sample of 113 respondents using a proportional random sampling technique. The instrument used was a questionnaire. The results showed that most of the self-concept of menopausal women was moderate, as many as 41 respondents (36.3%). The results of the self-concept component include the self-image of postmenopausal mothers mostly low by 60 respondents (53.1%), the ideal self of postmenopausal mothers is mostly moderate by 41 respondents (36.3%), the self-role of postmenopausal mothers is mostly high by 52 respondents (46%) , the self-identity of postmenopausal women was mostly moderate, as many as 46 respondents (40.7%), and the self-esteem of postmenopausal women was mostly low, as many as 61 respondents (54%). the self-concept of postmenopausal mothers is mostly in the moderate category. Suggestion: it is hoped that the family can provide support for menopausal women, besides that menopausal women can increase their self-confidence by participating in community and religious activities ABSTRAK Data Badan Pusat Statistik menunjukkan ada 15,2 juta wanita dari 118 juta mengalami menopause. Menopause tidak hanya ditandai dengan berhentinya menstruasi, wanita yang telah menopause juga mengalami banyak perubahan, mulai dari penampilan fisik, kondisi psikologis hingga hasrat seksual. Selain itu wanita yang sudah menopause juga tidak bisa hamil lagi. Perubahan yang terjadi ini dapat berdampak pada konsep diri ibu yang mengalaminya.Konsep diri terdiri dari citra diri, ideal diri, peran diri, identitas diri dan harga diri. mengetahui gambaran konsep diri ibu menopause di Desa Sumur. Jenis pendekatan kuantitatif dengan rancangan deskriptif. Populasi penelitian 157 ibu menopause di Desa Sumur dengan jumlah sampel 113 responden dengan teknik proposiaonal random sampling. Instrumen yang digunakan adalah kuesioner. Hasil penelitian didapatkan sebagian besar konsep diri pada ibu menopause adalah sedang sebanyak 41 responden (36.3%). Hasil dari komponen konsep diri mencakup citra diri ibu menopause sebagian besar rendah sebanyak 60 responden (53.1%), ideal diri ibu menopause sebagian besar sedang sebanyak 41 responden (36.3%), peran diri ibu menopause sebagian besar tinggi sebanyak 52 responden (46%), identitas diri ibu menopause sebagian besar sedang sebanyak 46 responden (40.7%), dan harga diri ibu menopause sebagian besar rendah sebanyak 61 responden (54%). konsep diri ibu menopause sebagian besar dalam kategori sedang. diharapkan keluarga dapat memberikan dukungan pada ibu menopause, selain itu ibu menopasue bisa meningkatkan percaya diri dengan mengikuti kegiatan-kegiatan masyrakat dan religi